The Representation of Malay Woman as Portrayed in H. Suhaimi’s Cik Puan - Essy Syam; Mita Rosaliza (Human Sustainability Procedia, 2018)
Malay society, a woman is placed to accept her weak or lower position than man’s. in some works and media, this representation is commonly found. Anyway, there are also found some works in Malay society which dismantle that stable universal representation. Malay woman is represented as smart, brave and strong opinion. On the surface, these representations label Malay woman with positive stereotypes, but clearly this text represents Malay woman negatively; Malay woman is represented as rude, sly and ambitious woman. So ,as a whole, Malay woman is represented negatively to describe that Malay woman who is in high position needs to be controlled because the woman in high position and the power tend to misuse the power and position.